Table of Content - - (Journal of Risk and Crisis Management, 2025)
Table of Content:1. The Impact of the National Strategy for Cybersecurity in Reducing the Risks of Accounting Information Systems - An Empirical Study on thy Saudi Governmental SectorMs. Nahed Abdullah Barasheed , Dr. Rawya Reda Obaid2. The Role of Leadership in Managing Risk to Ensure Project Success in the Arabian American Oil Company (Aramco) In Saudi Arabia from 2020 to 2024Mr. Badr Rashad Qablawi, Ms. Rawda Ayman Abuttahir
Keywords: Journal of Risk and Crisis Management